KAJIAN TRANSFORMASI SEMANTIK DALAM PORTFOLIO DESAIN PRODUK KEWIRAUSAHAAN SOSIAL - Devanny Gumulya; Isabela Elena (Jurnal Dimensi Seni Rupa dan Desain, 2020)
AbstractThe market is increasingly more competitive; a brand must have a strong product design identity. Famous brands such as Nike, Apple and Swatch are brands that are good at managing their portfolio strategy for a long time. These brands can form an absolute imagination in the consumer’s mind by orchestrating coherent design characters across their product portfolio. Therefore, a brand must consistently use its design elements without making it dull. Consistent but the novelty element remains essential in every product line. Social enterprise to carry out the societal mission should be able to keep up with other products on the market. Therefore, social enterprise ability to manage their product portfolio strategy is essential. Semantic transformation is the process of changing from language realm into the entity that can be physically seen through design features. It is the process of creating design feature to represent meaning. Three social enterprises: Borneo Chic, Noesa and Du’anyam were selected for semantic transformation analysis across its product portfolio, starting from the brand value into design feature from the product portfolio line. The results suggest that the meanings carried by social enterprises are locality, environmentally friendly and mission to build community capacity. These meanings are transformed into design features such as natural colour combinations, woven and weaving elements as a representation of the product made by local craftsmen and one of a kind not factory-made or mass-produced, use local material and environmentally friendly. The social enterprise is expected to innovate traditional features into something modern that fit to a modern lifestyle. Imperfections in social enterprise’s products are also anticipated because it shows that products are made by humans. AbstrakPersaingan pasar yang semakin ketat membuat sebuah brand harus memiliki identitas desain produk yang kuat. Brand-brand ternama seperti Nike, Apple dan Swatch adalah brand yang pandai mengatur strategi portofolionya sehingga dalam kurun waktu yang lama, brand-brand tersebut bisa membentuk imajinasi yang absolut akan karakter desain dari portofolio produknya. Oleh karena itu, sang brand harus secara konsisten menggunakan elemen-elemen desainnya tanpa membuatnya menjadi membosankan. Konsisten tapi unsur kebaruan tetap penting dalam setiap lini produk. Kewirausahaan sosial untuk menjalankan misi sosialnya, harus mampu bersaing dengan produk-produk lain yang ada di pasar. Oleh karena itu strategi portofolio dari kewirausahaan sosial menjadi sangat penting. Transformasi semantik adalah proses perubahan dari ranah bahasa menjadi wujud entitas yang dapat dlihat secara fisik melalui fitur-fitur desain yang diciptakan untuk merepresentasikan sebuah makna. Tiga kewirausahaan sosial berbasis desain produk: Borneo Chic, Noesa dan Dua’anyam dipilih untuk dianalisa transformasi semantiknya, bermula dari ranah bahasa brand value menjadi karakter desain dari lini portofolio produk. Hasil penelitian adalah makna-makna yang diusung kewirusahaan sosial adalah lokalitas, ramah lingkungan dan misi pembangungan kapasitas komunitas. Makna ini ditranslasikan dalam fitur-fitur desain seperti kombinasi warna natural, elemen anyaman dan tenun sebagai representasi produk yang dibuat oleh perajin lokal dan bukan buatan pabrik atau produksi massa. Material yang digunakan lokal dan ramah lingkungan. Wirausaha sosial diharapkan untuk menginovasi fitur tradisional menjadi sesuatu yang tidak biasa. Ketidaksempurnaan pada produk kewirausahaan juga diantisipasi karena menunjukan bahwa produk dibuat oleh manusia.